Investigating cell lineage specific biosynthesis of tenascin-C during inflammation - Giblin, S (2018)
The extracellular matrix (ECM) is a complex network of molecules secreted by cells, which is essential for providing structural support and facilitating cell processes including adhesion, migration and survival. Tenascin-C is an immunomodulatory ECM protein that exhibits limited expression in healthy tissues, but is transiently elevated at sites of tissue injury, and is persistently expressed in chronic inflammatory diseases and tumours. Alternative splicing of 9 of tenascin-C's fibronectin type III-like domains (FnIII- A1, A2, A3, A4, B, AD2, AD1, C and D) generates enormous diversity in form; yielding 511 possible isoforms. Post-transcriptional modification of tenascin-C has been studied in cancer and during development where disease and tissue specific isoforms exhibit distinct adhesive, migratory and proliferative effects. However, little is known of how tenascin-C is expressed or alternatively spliced during inflammation. This study characterises inflammation and disease specific tenascin-C isoforms made by immune cells and fibroblasts, and investigates their functional relevance. Biosynthesis and alternative splicing of tenascin-C was examined using standard curve qPCR, ELISA, Western blot and confocal immunocytochemistry in resting and activated primary human immune cells, dermal fibroblasts, and in synovial fibroblasts isolated from healthy controls and from osteoarthritis (OA) and rheumatoid arthritis (RA) patients. Based on these data, three recombinant proteins comprising FnIII domains AD2-AD1, B-C-D and B-AD2-AD1-C-D were cloned, expressed and purified, and their impact on cell behaviour including adhesion, morphology and migration was assessed. Basal tenascin-C expression was lower in myeloid and lymphoid cells than fibroblasts, and was induced in all following inflammatory stimulation. Tenascin-C expression was elevated in disease with RA and OA synovial fibroblasts containing higher levels than healthy controls. Alternative splicing following cell activation was cell-type specific: all FnIII except AD2 and AD1 were upregulated in dendritic cells and macrophages, in T-cells all FnIII remained unchanged with FnIII A1 absent; and no change in splicing was observed in activated dermal fibroblasts. Normal and OA synovial fibroblasts exhibited similar tenascin-C splicing patterns, but FnIII B and D were specifically elevated in RA. Functional analysis revealed differences in the adhesion, morphology and migration of myeloid cells and dermal fibroblasts cultured on FnIII AD2-AD1, B-C-D, B-AD2-AD1-C-D and full length tenascin-C substrates; FnIII B-C-D promoted MDDC migration while B-AD2-AD1-C-D promoted fibroblast adhesion, compared to full length tenascin-C. For the first time, this study reveals differences in tenascin-C biosynthesis and alternative splicing by immune cells and fibroblasts following activation with inflammatory stimuli; and starts to reveal how alternative splicing of tenascin-C may influence the behaviours of both stromal and immune cells types during inflammation and in inflammatory diseases.